2016
DOI: 10.1088/0953-8984/28/29/293002
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity in alkali metal intercalated iron selenides

Abstract: Alkali metal intercalated iron selenide superconductors A x Fe2-y Se2 (where A  =  K, Rb, Cs, Tl/K, and Tl/Rb) are characterized by several unique properties, which were not revealed in other superconducting materials. The compounds crystallize in overall simple layered structure with FeSe layers intercalated with alkali metal. The structure turned out to be pretty complex as the existing Fe-vacancies order below ~550 K, which further leads to an antiferromagnetic ordering with Néel temperature fairly above ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 232 publications
5
38
0
Order By: Relevance
“…Since the L 2,3 absorption spectrum results from the excitation of electrons from the core Fe 2p levels to unoccupied 3d states, these spectra are sensitive to the local bonding environment of Fe. The core-hole spin-orbit interaction leads to splitting of the final state into two manifolds corresponding to j = 3 2 and 1 2 , which are well separated in energy, resulting in the L 3 and L 2 structures at 707 and 720 eV, respectively. The branching ratio…”
Section: Peem Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Since the L 2,3 absorption spectrum results from the excitation of electrons from the core Fe 2p levels to unoccupied 3d states, these spectra are sensitive to the local bonding environment of Fe. The core-hole spin-orbit interaction leads to splitting of the final state into two manifolds corresponding to j = 3 2 and 1 2 , which are well separated in energy, resulting in the L 3 and L 2 structures at 707 and 720 eV, respectively. The branching ratio…”
Section: Peem Studymentioning
confidence: 99%
“…The coexistence of superconductivity and antiferromagnetism has been observed in many iron-based compounds, and the intriguing balance between competing magnetic interactions is thought to be the key to understanding the origins of unconventional superconductivity. Alkali-metal-doped iron selenides (A x Fe 2−y Se 2 , A = K, Cs, Rb) are an extreme example, exhibiting superconducting properties up to the relatively high temperature of about 30 K and, simultaneously, antiferromagnetic ordering that persists up to temperatures as high as 500 K [1,2]. Microstructural studies have revealed that superconducting single crystals of these compounds are intrinsically phase separated, with a striking microstructure consisting of a three-dimensional array of the minority phase in the form of plates aligned along the crystallographic {103} planes [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…It is generally believed that superconductivity in this system appears in an ideal 122-type structure, though most of the samples studied so far were multiphase, consisting of a mixture of mesoscopic superconducting and insulating (antiferromagnetic) structures (e.g. such as K 2 Fe 4 Se 5 ), complicating the studies of this system [12].…”
Section: Introductionmentioning
confidence: 99%
“…Further success in creation of intercalated FeSe based systems with rather high T c ∼ 30-40K (see review in [8,9]) quickly made them popular objects of investigations because of their different electronic structure [10,11].…”
Section: Introductionmentioning
confidence: 99%